Evaluation of Topicure® Plus spray on sheep infested with Myiasis - Selvam, Ramasamy; Suresh, Subramaniyam; Prashanth, DSouza (Asian Journal of Medical and Biological Research, 2017)
The present study was designed to evaluate the therapeutic efficacy of polyherbal aerosol spray - Topicure® Plus against maggot infested wounds in sheep. Two sheep presented at Vellore Veterinary Dispensary with a history of maggot infested wound were selected. Based on the severity of wound, antibiotics (Ampicillin - 10 mg/kg body weight) and NSAIDs (Meloxicam - 0.5 mg/kg body weight on 1st day) were administered. The site of wound was clipped off the hair and cleaned with sterile saline solution and wiped with dry sterile cotton on first day of the treatment. Then Topicure® Plus was sprayed in sufficient quantities to cover the entire wound twice daily till complete healing of wound occurs. When Topicure® Plus spray was administered concurrent local treatment with other fly repellents/maggoticidal agents was not followed. Wound was observed for the changes in swelling, discharge, granulation tissue and wound healing process following the treatment till complete recovery. Similarly, fly repellent activity and duration, maggot repellent property, activity level and product satisfaction score were also recorded. The results indicate that Topicure® Plus had ensured faster wound healing (within 8 days) which is evident through reduction in pain, swelling, discharge and granulation tissue score along with superior fly repellent activity and duration, maggot repellent property. Therefore, it appears from the present study that treatment of myiasis wound with Topicure® Plus spray along with antibiotic regime was the most effective in field conditions as it avoids the day to day manual removal of maggots and induces the faster wound healing. Asian J. Med. Biol. Res. June 2017, 3(2): 216-220